2016
DOI: 10.1002/art.39618
|View full text |Cite
|
Sign up to set email alerts
|

Aging Promotes Sirtuin 3–Dependent Cartilage Superoxide Dismutase 2 Acetylation and Osteoarthritis

Abstract: Objective To quantify functional age-related changes in the cartilage antioxidant network to discover novel mediators of cartilage oxidative stress and osteoarthritis (OA) pathophysiology. Methods We evaluated knee OA histopathology in 10, 20, and 30-month old male F344BN rats and analyzed cartilage oxidation by the ratio of reduced:oxidized glutathione. Antioxidant gene expression and protein abundance were analyzed by qRT-PCR and selected reaction-monitoring mass spectrometry, respectively. Superoxide dism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 51 publications
2
86
0
Order By: Relevance
“…Cartilage SIRT-3 expression was also recently shown to decrease with age, and SIRT-3 deficiency increases acetylation of the antioxidant enzyme SOD2, resulting in impaired SOD2 activity in chondrocytes (75). In addition, whole-body deletion of SIRT-3 accelerates the development of knee OA (75). Expression of SIRT-6 is significantly decreased in human OA chondrocytes as well (76).…”
Section: Berenbaum Et Almentioning
confidence: 99%
“…Cartilage SIRT-3 expression was also recently shown to decrease with age, and SIRT-3 deficiency increases acetylation of the antioxidant enzyme SOD2, resulting in impaired SOD2 activity in chondrocytes (75). In addition, whole-body deletion of SIRT-3 accelerates the development of knee OA (75). Expression of SIRT-6 is significantly decreased in human OA chondrocytes as well (76).…”
Section: Berenbaum Et Almentioning
confidence: 99%
“…Genome‐wide DNA methylation changes have been shown in hip and knee cartilage in human osteoarthritis patients and have been linked to differential expression of 70 genes, including the osteoarthritis‐associated genes VIT , ROR2 , and WLS . Altered activity of the Sirtuin family of histone deacetylases, in particular SIRT1, SIRT3, and SIRT6, has also been implicated in arthritis . In particular, increased histone acetylation within articular cartilage has been linked to ectopic hypertrophy in the mouse knee, including increased expression of matrix metalloproteases (e.g., MMP‐13) that degrade joint cartilage …”
Section: Developmental Pathways In Adult Joint Diseasementioning
confidence: 99%
“…Protein acetylation in mitochondria typically promotes decreased mitochondrial integrity and function (6).The nicotinamide adenine dinucleotide (NAD + )-dependent protein deacetylase, SIRT3 (Sirtuin 3), is the major mitochondrial protein deacetylase localized to the mitochondria (7,8), thereby regulating mitochondrial antioxidant system and OXPHOS (9,10). SIRT3 protects mitochondria from oxidative stress by deacetylating superoxide dismutase (SOD2) and mitigates OA progression (11). Chen et al recently showed that SIRT3 was regulated by AMP-activated protein kinase (AMPK) activation in human chondrocytes, which reduced mtDNA 4977 deletion and improved mitochondrial functions (12).…”
Section: Introductionmentioning
confidence: 99%